The challenges of pricing quantity surveying professional services in Ghana - Michael Adesi; Degraft Owusu-Manu; Frank Boateng; Michael Nii Addy; Ernest Kissi (Frontiers in Engineering and Built Environment, 2023)
Purpose – The purpose of this study is to investigate the challenges of pricing quantity surveying (QS) professional services to enhance the understanding of practitioners in developing strategies for the determination of fees for their services. Design/methodology/approach – The paper adopts the quantitative approach by administering 150 survey questionnaires QS professionals out of which 79 questionnaires were retrieved for analysis using the mean, standard deviation, standard error and the Chi-Square test. Findings – The study identified the challenges that continue to hamper the successful pricing of QS services as the inability to respond to changing contractual arrangements; lack of appropriate response to emerging services; slow response to changes in information and communication technology. Research limitations/implications – This paper focused on QS professionals. Hence, a future study to encompass other professionals in the built environment will be novel. Practical implications – The findings of this paper have the potential to motivate QS firms to develop solutions that address the challenges identified to improve the efficiency of their service delivery to clients. The paper also has the practical importance of opening up new frontiers of research that focus on pricing of professional services in the built environment in general. Originality/value – The paper contributes to the awareness and understanding of QS professionals about the challenges that continue to hamper effective pricing of their services.